THE IMAGE OF THE MOTHERLAND IN THE POETRY OF FARIZA ONGARSYNOVA: Received: 04th October 2021; Revised: 09th January 2022, 23th February 2022, 25th February 2022; Accepted: 26th February 2022 - Kamarova, N S (PEOPLE: International Journal of Social Sciences, 2022)
The article examines the image of the Motherland in the poetry of the Kazakh famous poetess Fariza Ongarsynova. Here is revealed the connection of poetess’s poems with folklore works. It is argued that Mangystau, the poetess’s small homeland, is the source of her poetic inspiration. The idea is substantiated that the image of a small homeland occupies a special place in the work of the Kazakh poetess. It is also noted that the lyrical hero of the poetess’s works feels like a part of his native land, its nature and destiny. Thanks to the study of the characteristic poetic feature of Fariza Ongarsynova, it is possible to recognize her poetic skill. Artistic individuality, ideological and thematic themes of poetry, contribution to the national artistic tradition, the corresponding place and figurative character occupied in modern Kazakh poetry will be studied.